Pengaruh Teknik Pembelajaran dan Kreativitas terhadap Hasil Belajar Matematika - Nur Amalia (Universitas Indraprasta PGRI, 2015)
The aim of the research was to analyze: (1) the effect of learning technique on mathematics achievement, (2) the effect of creativity on mathematics achievement, and (3) interaction effect of learning technique and creativity on mathematics achievement. The research was conducted in State Junior High School in Kebon Jeruk, West Jakarta. Research method used quasi experiment with anava two ways. Population was 220 students at the eight grades of Junior High School 220 Jakarta and Junior High School 127 Jakarta. Sample was taken with multistage sample, which consist of 48 students which consist of 24 students at eight grade of Junior High School 220 Jakarta and 24 students of Junior High School 127 Jakarta. Instrument that is used in this research are questionnairs about creativity and mathematics achievement. Test hipothesis used anava two ways. Based on the result of the research it can be concluded that: (1) there is an effect of learning technique on mathematics achievement, (2) there is an effect of creativity on mathematics achievement, and (3) there isn’t interaction effect of learning technique and creativity on mathematics achievement. Hopefully teacher has an ability to choose and create learning mathematics which can improve mathematics achievement and creativity, one of them is learning iconic.